Multi-scale experimental investigation and analytical micro-mechanical modeling to determine Young's modulus of alkali-activated slag concrete. (20th June 2023) - Caron, Richard; Patel, Ravi A.; Bogner, Andreas; Dehn, Frank
Abstract: In this study, multi-scale experiments and analytical micro-mechanics based modeling are conducted to evaluate Young's modulus of alkali-activated slag (AAS) concrete. The evolution of volume fractions of phases is obtained using a thermodynamic model coupled with a kinetic model. Nano-indentation measurements indicate the existence of a soft and a hard matrix made of reaction products, independently of the mix tested. The homogenization model for Young's modulus is validated against results on paste and concrete with more than 95 % accuracy. Sensitivity analysis reveals Young's modulus of aggregates and of the soft matrix as the main influencing parameters. Highlights: The reaction product foam of AAS is made of two matrices, one softer and one harder. Reaction products proportion and properties at nano-scale are independent of mix. Multi-scale modeling accurately predicts AAS Young's modulus of paste and concrete. Young's modulus is more sensitive to changes in activator than slag composition. Young's modulus of soft matrix and aggregates are the most influential parameters.